Study of physical properties of zinc oxide thin films using the hydrothermal method - Elfadel Tayfor, Montasir Salman (JOURNAL OF ADVANCES IN PHYSICS, 2024)
Zinc oxide (ZnO) is a versatile semiconductor material with unique physical, chemical, and optical properties. It has garnered significant attention in recent years due to its wide applications in electronics, photonics, sensors, and environmental devices. This paper provides a comprehensive review of the fundamental properties of ZnO, its synthesis methods, and the wide range of applications it enables. The focus is on the material’s electronic properties, optical characteristics, and how these features are being leveraged in innovative technologies such as transparent conductors, UV detectors, and gas sensors.